Hubungan Kecepatan Angin dan Kelembaban Udara terhadap Pemencaran Konidium Cercospora nicotianae pada Tembakau - RAFIQI TANTAWI, AHMAD (AGRITROP, 2007)
One of the limiting factors in tobacco production is frogeye leaf spot, a fungal disease caused by C. nicotianae.Epidemic of this disease was supposed to have a close relationship with weather aspects, such as wind velocity,temperature, solar radiation intensity and relative humidity. An experiment was conducted to determine relationshipbetween wind velocity and relative humidity to conidial dispersal on tobacco. The experiment carried out at MycologyLaboratory, Study Program of Plant Pest and Disease, Faculty of Agriculture, UGM and two tobacco plantations inJember and Klaten. The results showed that conidia was dispersed by wind and can be trapped by Kiyosawa typeof wind vane rotary spore trap. Conidia were dispersed in dry, and moist, as well as wet months. During the dryand moist month, conidia was trapped since 06.00 a.m. the trapping reached its peak at 02.00-06.00 p.m., while inwet month at 10.00 a.m. to 14.00 p.m. Dry air condition was needed in conidium releasing. The number of conidiawas decreased when relative humidity increased.